2022
DOI: 10.3390/plants11050695
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Creation of Interspecific Hybrid Progeny to Broaden Genetic Distance through Double Haploid (DH) Inducer in Brassica napus

Abstract: Interspecific hybridization of rapeseed is an important way to innovate breeding resources. This research used Brassica napus and Brassica rapa for artificial synthesis interspecific hybridization of F1. The F1 self-fruiting rate was particularly low. By comparing the fertilization rate and seed setting rate of nine crosses and selfing combinations of interspecific hybrid progeny F1 and control B. napus, the results proved that the genetic stability of egg cells was greater than that of sperm cells, so the F1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The ploidy level typical of the female plants used in the crosses was confirmed by flow cytometry and SNP chip technology. Building upon these previous results, Zhou et al [266] obtained interspecific maternal inbred offspring from egg cells of B. napus pollinated with the pollen of the DH inducer named Y3380. The FISH results confirmed that the obtained F 1 was B. napus (2n = 4x = 38, genome AACC).…”
Section: Dicot Speciesmentioning
confidence: 94%
See 1 more Smart Citation
“…The ploidy level typical of the female plants used in the crosses was confirmed by flow cytometry and SNP chip technology. Building upon these previous results, Zhou et al [266] obtained interspecific maternal inbred offspring from egg cells of B. napus pollinated with the pollen of the DH inducer named Y3380. The FISH results confirmed that the obtained F 1 was B. napus (2n = 4x = 38, genome AACC).…”
Section: Dicot Speciesmentioning
confidence: 94%
“…In the genus Brassica, difficulties have often been encountered in obtaining welldeveloped embryos from interspecific hybridizations. For example, interspecific hybridization between Brassica napus and B. rapa resulted in a low hybridization rate [266]. A comparison between interspecific hybridization and self-fertilization materials demonstrated that egg cells' genetic stability was greater than sperm cells.…”
Section: Dicot Speciesmentioning
confidence: 99%
“…We counted the fertilization rate 48 h after pollination. Fertilization rate percentage was calculated by the following formula: fertilization rate % = the number of ovules with fluorescent dots in the silique/total number of ovules in the silique × 100 ( Zhou et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [88] developed cytoplasmic male sterile and maintainer lines of B. napus with the doubled haploid inducer allooctoploid lines Y3380 and Y3560 described above. Zhou et al [89] hypothesized that the new DH inducer lines can successfully replace the method of continuous backcrossing of interspecific F 1 with the parent to resolve the problem of low seed rate. Such difficulty is caused by hybrid sterility and chromosomal mismatch in the hybrid offspring of rapeseed.…”
Section: Brassica Napus Haploid Production Via Interploidy Hybridizationmentioning
confidence: 99%